Carbonate-associated fluorescent dissolved organic matter (CAFDOM): Establishing a new proxy for dissolved organic matter in ancient oceans - Wei Wang; Chao Li; Matthew S. Dodd; Hao Xu; Meng Cheng; Zihu Zhang; Chunxia Yang; Jun Hu; Haiyang Wang; Xinyang Chen; Adrian Immenhauser (Geochimica et Cosmochimica Acta, 2026)

Aerated digestate management enhances soil properties, reduces greenhouse gas emissions, and shifts microbial communities - Tannu Kumari; James O'Connor; Yunyun Zheng; Ali Huxtable; Matthew S. Dodd; Sasha N. Jenkins; Bede S. Mickan (Journal of Environmental Management, 2026)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Heterogeneous coupling of δ13Corg and δ13Ccarb during the Shuram Excursion: Implications for a large dissolved organic carbon reservoir in the Ediacaran ocean - Haodong Gu; Jun Hu; Meng Cheng; Haiyang Wang; Matthew S. Dodd; Zihu Zhang; Thomas J. Algeo; Chao Li (Global and Planetary Change, 2024)

Editorial preface to special issue: The Earth System during icehouse Climate Modes: Evidence from glacial records in China - Xianguo Lang; Bing Shen; Jitao Chen; Matthew Dodd (Global and Planetary Change, 2024)

Integrated Stratigraphy and Mineralogy of the Doushantuo Formation in Weng’an, South China, and Implications for Ediacaran Phosphogenesis - Liangxuan Jiao; Zhenbing She; Dominic Papineau; Yaguan Zhang; Matthew S. Dodd; Kenan Cao; Qun Chen; Guoyong Chen (Journal of Earth Science, 2024)

Construction of relatedness matrices in autopolyploid populations using low-depth high-throughput sequencing data - Timothy P. Bilton; Sanjeev Kumar Sharma; Matthew R. Schofield; Michael A. Black; Jeanne M. E. Jacobs; Glenn J. Bryan; Ken G. Dodds (Theoretical and Applied Genetics, 2024)
Key message An improved estimator of genomic relatedness using low-depth high-throughput sequencing data for autopolyploids is developed. Its outputs strongly correlate with SNP array-based estimates and are available in the package GUSrelate. Abstract High-throughput sequencing (HTS) methods have reduced sequencing costs and resources compared to array-based tools, facilitating the investigation of many non-model polyploid species. One important quantity that can be computed from HTS data is the genetic relatedness between all individuals in a population. However, HTS data are often messy, with multiple sources of errors (i.e. sequencing errors or missing parental alleles) which, if not accounted for, can lead to bias in genomic relatedness estimates. We derive a new estimator for constructing a genomic relationship matrix (GRM) from HTS data for autopolyploid species that accounts for errors associated with low sequencing depths, implemented in the R package GUSrelate. Simulations revealed that GUSrelate performed similarly to existing GRM methods at high depth but reduced bias in self-relatedness estimates when the sequencing depth was low. Using a panel consisting of 351 tetraploid potato genotypes, we found that GUSrelate produced GRMs from genotyping-by-sequencing (GBS) data that were highly correlated with a GRM computed from SNP array data, and less biased than existing methods when benchmarking against the array-based GRM estimates. GUSrelate provides researchers with a tool to reliably construct GRMs from low-depth HTS data.

Heterogeneous sulfide reoxidation buffered oxygen release in the Ediacaran Shuram ocean - Wei Shi; Benjamin J.W. Mills; Thomas J. Algeo; Simon W. Poulton; Robert J. Newton; Matthew S. Dodd; Zihu Zhang; Lei Zheng; Tianchen He; Mingcai Hou; Chao Li (Geochimica et Cosmochimica Acta, 2023)

A DOM regulation model for dolomite versus calcite precipitation in the Ediacaran ocean: Implications for the “dolomite problem” - Wei Wang; Chao Li; Matthew S. Dodd; Thomas J. Algeo; Zihu Zhang; Meng Cheng; Mingcai Hou (Precambrian Research, 2023)

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

One beach amongst many: how weak fidelity to a focal nesting site can bias demographic rates in marine turtles - Joseph B. Pfaller; Sara M. Weaver; Kristina L. Williams; Mark G. Dodd; Matthew H. Godfrey; DuBose B. Griffin; S. Michelle Pate; C. George Glen; Campbell J. Nairn; Brian M. Shamblin (Marine Biology, 2022)

Ecosystem Services: Delivering Decision-Making for Salt Marshes - Philine S. E. zu Ermgassen; Ronald Baker; Michael W. Beck; Kate Dodds; Sophus O. S. E. zu Ermgassen; Debbrota Mallick; Matthew D. Taylor; R. Eugene Turner (Estuaries and Coasts, 2021)

In search of the “missing majority” of nesting loggerhead turtles: improved inter-seasonal recapture rates through subpopulation-scale genetic tagging - Brian M. Shamblin; Mark G. Dodd; S. Michelle Pate; Matthew H. Godfrey; Joseph B. Pfaller; Kristina L. Williams; Breanna L. Ondich; David A. Steen; Elizabeth S. Darrow; Paul Hillbrand; Ruth Boettcher; Michael S. Coyne; et al. (Marine Biology, 2021)

What can seabirds tell us about the tide? - Matthew Cooper; Charles Bishop; Matthew Lewis; David Bowers; Mark Bolton; Ellie Owen; Stephen Dodd (Ocean Science, 2018)
Small global positioning system (GPS) trackers are now routinely used to study the movement and behaviour of birds at sea. If the birds rest on the water they become “drifters of opportunity” and can be used to give information about surface currents. In this paper, we use a small data set from satellite-tracked razorbills (Alca torda) in the Irish Sea to test the potential of this idea for measuring tidal currents. Razorbills regularly rest on the sea overnight and their tracks at this time are consistent with their drifting with the tidal flows and changing direction as the flood turns to ebb and vice versa. Data from 4 years (2011–2014) have been binned in a geographical grid and analysed to give the variation of current over a mean tidal cycle in each grid element. A map of maximum current speed is consistent with a numerical model of the tidal currents in the region. The root mean square difference between observed maximum speed and that predicted by the model is 0.15 m s−1, about 15 % of typical current speeds in the area. The divergence between bird-track speed and model prediction increases in regions of the fastest tidal currents. The method clearly has its limitations, but the results of this study show that tagged birds resting on the sea have potential to provide relatively inexpensive quantitative information about surface tidal currents over an extended geographical area.

A condition metric for Eucalyptus woodland derived from expert evaluations - Steve J. Sinclair; Matthew J. Bruce; Peter Griffioen; Amanda Dodd; Matthew D. White (Conservation Biology, 2018)
The evaluation of ecosystem quality is important for land‐management and land‐use planning. Evaluation is unavoidably subjective, and robust metrics must be based on consensus and the structured use of observations. We devised a transparent and repeatable process for building and testing ecosystem metrics based on expert data. We gathered quantitative evaluation data on the quality of hypothetical grassy woodland sites from experts. We used these data to train a model (an ensemble of 30 bagged regression trees) capable of predicting the perceived quality of similar hypothetical woodlands based on a set of 13 site variables as inputs (e.g., cover of shrubs, richness of native forbs). These variables can be measured at any site and the model implemented in a spreadsheet as a metric of woodland quality. We also investigated the number of experts required to produce an opinion data set sufficient for the construction of a metric. The model produced evaluations similar to those provided by experts, as shown by assessing the model's quality scores of expert‐evaluated test sites not used to train the model. We applied the metric to 13 woodland conservation reserves and asked managers of these sites to independently evaluate their quality. To assess metric performance, we compared the model's evaluation of site quality with the managers’ evaluations through multidimensional scaling. The metric performed relatively well, plotting close to the center of the space defined by the evaluators. Given the method provides data‐driven consensus and repeatability, which no single human evaluator can provide, we suggest it is a valuable tool for evaluating ecosystem quality in real‐world contexts. We believe our approach is applicable to any ecosystem.

Improved female abundance and reproductive parameter estimates through subpopulation-scale genetic capture-recapture of loggerhead turtles - Brian M. Shamblin; Mark G. Dodd; DuBose B. Griffin; S. Michelle Pate; Matthew H. Godfrey; Michael S. Coyne; Kristina L. Williams; Joseph B. Pfaller; Breanna L. Ondich; Kimberly M. Andrews; Ruth Boettcher; Campbell J. Nairn (Marine Biology, 2017)

Take-all decline in New Zealand wheat soils and the microorganisms associated with the potential mechanisms of disease suppression - Soonie Chng; Matthew G. Cromey; Sarah L. Dodd; Alison Stewart; Ruth C. Butler; Marlene V. Jaspers (Plant and Soil, 2015)

Evaluating the landscape of fear between apex predatory sharks and mobile sea turtles across a large dynamic seascape - Neil Hammerschlag; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark Dodd; Michael G. Frick; Matthew H. Godfrey; Brendan J. Godley; DuBose B. Griffin; Kyra Hartog; Sally R. Murphy; Thomas M. Murphy; et al. (Ecology, 2015)
The “landscape of fear” model has been proposed as a unifying concept in ecology, describing, in part, how animals behave and move about in their environment. The basic model predicts that as an animal's landscape changes from low to high risk of predation, prey species will alter their behavior to risk avoidance. However, studies investigating and evaluating the landscape of fear model across large spatial scales (tens to hundreds of thousands of square kilometers) in dynamic, open, aquatic systems involving apex predators and highly mobile prey are lacking. To address this knowledge gap, we investigated predator–prey relationships between tiger sharks ( Galeocerdo cuvier ) and loggerhead turtles ( Caretta caretta ) in the North Atlantic Ocean. This included the use of satellite tracking to examine shark and turtle distributions as well as their surfacing behaviors under varying levels of home range overlap. Our findings revealed patterns that deviated from our a priori predictions based on the landscape of fear model. Specifically, turtles did not alter their surfacing behaviors to risk avoidance when overlap in shark–turtle core home range was high. However, in areas of high overlap with turtles, sharks exhibited modified surfacing behaviors that may enhance predation opportunity. We suggest that turtles may be an important factor in determining shark distribution, whereas for turtles, other life history trade‐offs may play a larger role in defining their habitat use. We propose that these findings are a result of both biotic and physically driven factors that independently or synergistically affect predator–prey interactions in this system. These results have implications for evolutionary biology, community ecology, and wildlife conservation. Further, given the difficulty in studying highly migratory marine species, our approach and conclusions may be applied to the study of other predator–prey systems.

Neuromuscular electrical stimulation via the peroneal nerve is superior to graduated compression socks in reducing perceived muscle soreness following intense intermittent endurance exercise - Richard A. Ferguson; Matthew J. Dodd; Victoria R. Paley (European Journal of Applied Physiology, 2014)

Foraging habitats and migration corridors utilized by a recovering subpopulation of adult female loggerhead sea turtles: implications for conservation - DuBose B. Griffin; Sally R. Murphy; Michael G. Frick; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark G. Dodd; Matthew H. Godfrey; Brendan J. Godley; Lucy A. Hawkes; Thomas M. Murphy; Kristina L. Williams; et al. (Marine Biology, 2013)

Genetic structure of the southeastern United States loggerhead turtle nesting aggregation: evidence of additional structure within the peninsular Florida recovery unit - Brian M. Shamblin; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Anton D. Tucker; Chris Johnson; Raymond R. Carthy; Russell A. Scarpino; Erin McMichael; David S. Addison; Kristina L. Williams; Michael G. Frick; et al. (Marine Biology, 2011)